The significance of pork as a source of dietary selenium - an evaluation of the situation in the Czech Republic - Fajt, Zdeněk; Drábek, Josef; Steinhauser, Ladislav; Svobodová, Zdeňka (Neuro-endocrinology letters, 2009)
The aim of this paper is to review current knowledge of the significance of pork as a source of Se for human consumption, and to evaluate the selenium content in pork produced in the Czech Republic. Selenium has an important role in human health. Pork could possibly be an important source of Se for the human diet. The Se content in meat can be increased by a higher dietary intake of selenium in animal feed. The magnitude of this increase is higher when organic Se from Se-enriched yeast is ingested. Selenium intoxication in pigs occurs only when very high Se concentrations are used in their diet (more than 5 mg/kg of Se). Organic Se sources produce fewer clinical signs of high toxicity than inorganic sodium selenite. Organic Se does not have a negative effect on meat quality. Altogether, 135 pork samples from 9 different herds in the Czech Republic were collected and analyzed for Se content. The average selenium content found in pork in our study was 87.10 microg/kg. Because the average annual consumption of pork in the Czech Republic is 42.0 kg per person, the annual selenium intake from pork represents 18.2% of the minimum yearly requirement for humans. The results of our study show that pork contributes significantly to the selenium intake of the human population in the Czech Republic.
Keywords: Česká republika; dieta; prasata; Diet; Swine; Czech Republic; Selenium; Meat; Animals; selen; lidé; maso; Humans; zvířata